O ativismo judicial e seus impactos em uma sociedade democrática de direito - Re Junior, Gaetano (2020)
This article aims to address judicial activism, an expression widely used in North American law, and its main characteristics. Theoretical concepts on the topic will be established, taking into account the judge's individual autonomy in making his decisions and respect for the constitutional rule. A study will be presented that addresses the judicialization of politics, as well as a comparative analysis of activism in relation to the control of constitutionality by the Federal Supreme Court. Historical judgments of the American Court in the post-civil war period will be analyzed, where they were in full racial segregation and Brazilian activism in the edition of the STF summary no. 13